Age-Associated Weight Gain, Leptin, and SIRT1: A Possible Role for Hypothalamic SIRT1 in the Prevention of Weight Gain and Aging through Modulation of Leptin Sensitivity - Sasaki, Tsutomu (Frontiers in Endocrinology, 2015)
The hypothalamus is the principal regulator of body weight and energy balance. It modulates both energy intake and energy expenditure by sensing the energy status of the body through neural inputs from the periphery as well as direct humoral inputs. Leptin, an adipokine, is one of the humoral factors responsible for alerting the hypothalamus that enough energy is stored in the periphery. Plasma leptin levels are positively linked to adiposity; leptin suppress energy intake and stimulates energy expenditure. However, prolonged increases in plasma leptin levels due to obesity cause leptin resistance, affecting both leptin access to hypothalamic neurons and leptin signal transduction within hypothalamic neurons. Decreased sensing of peripheral energy status through leptin may lead to a positive energy balance and gradual gains in weight and adiposity, further worsening leptin resistance. Leptin resistance, increased adiposity, and weight gain are all associated with aging in both humans and animals. Central insulin resistance is associated with similar observations. Therefore, improving the action of humoral factors in the hypothalamus may prevent gradual weight gain, especially during middle age. SIRT1 is a NAD+-dependent protein deacetylase with numerous substrates, including histones, transcription factors, co-factors, and various enzymes. SIRT1 improves both leptin sensitivity and insulin sensitivity by decreasing the levels of several molecules that impair leptin and insulin signal transduction. SIRT1 and NAD+ levels decrease with age in the hypothalamus; increased hypothalamic SIRT1 levels prevent age-associated weight gain and improve leptin sensitivity in mice. Therefore, preventing the age-dependent loss of SIRT1 function in the hypothalamus could improve the action of humoral factors in the hypothalamus as well as central regulation of energy balance.